If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(x + -5) = 5 Reorder the terms: 2x + 3(-5 + x) = 5 2x + (-5 * 3 + x * 3) = 5 2x + (-15 + 3x) = 5 Reorder the terms: -15 + 2x + 3x = 5 Combine like terms: 2x + 3x = 5x -15 + 5x = 5 Solving -15 + 5x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5x = 5 + 15 Combine like terms: -15 + 15 = 0 0 + 5x = 5 + 15 5x = 5 + 15 Combine like terms: 5 + 15 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| cot^2x=1 | | 4x+12-4=12x+8 | | 6x-5+2x=4(2x-1)-1 | | x+x+x=75 | | 5x+x^2=156 | | n+10=2 | | F(x)=6x-x^2+8 | | 9b^2-27b+18=0 | | 5+5b-3=2+5b | | -4w-7k=28fork | | 5x-6=3x-6+2x | | ln(8x)=3.9 | | 3t+7=3t+6 | | 5h^2+8h-85=0 | | (Y-9)-(Y+3)=5Y | | 13x-3x=2x+3 | | 5x=10-3[2x-5(x+8)] | | (Y-7)-(Y+4)=10Y | | 6x+11=12-7x | | X+2x=50+90+10 | | p-10=-10 | | y-3=6(x+1) | | 3(4m-5)=124m | | 2*x+1=2+2x | | (15b-1)-7(2b+2)=-6 | | 7x+4x+3+9=6x+3+4x | | x+7*2=3x+5 | | 10b+3+4= | | 12-7x=6x+11 | | 96+122=180 | | x+(x-48700)=284790 | | f(4)=10-.25*4 |